Course syllabus ontology for supporting e-learning program - Ta'a, Azman (2019)
In current information technology, every researcher put his effort to minimize the effects of having a huge amount of processed data, but in the same time the data could be produced by the users was not used and took a large space. The information was generated by different resources in different fields such as industries, telecommunications, and education. Therefore, this project is focused on the educational field, and in more specific is the syllabus of courses and how is it going to be defined and stored, which each component has a link to another component. Therefore, the student will be aware of the contents of the courses, and how each component was related to each other to form a better information to the student and lecturer. This will generate a clear picture for the students and lecturer on the course before the learning process started. The Protégé-OWL and SPARQL tools were used to develop the course syllabus ontology, and the evaluation of prototype application's usability has shown the increase of awareness of course content accessibility among the students and lecturers.